ECO Report Analys Achieving SDG 15 - A. Sankaran; Kameshwaran S; Aravind R.; Nandhakumaran T; Bharan (International Journal of Land, 2025)
This project creates automated data processing tool Eco Data Analyser for ecological data analysis for SDG 15: Life on Land conservation and biodiversity. File_picker, Excel, and CSV are used in the Flutter and Dart based cross-platform solution to assist environmental organizations in handling ecological data. Uploading ecological datasets, verifying data, classifying biodiversity indicators, and producing summary reports helps Eco Data Analyser to make conservation data accessible and valuable. User-defined parameters including region, habitat type, and species category guide processing of ecological data from Excel files. For geographical and time period comparisons, it standardizes data inputs to provide measuring unit and format consistency. Key tasks include species identification under risk, habitat biodiversity index computation, and data management including missing values. Data is exported and kept in CSV format via HTTP POST requests after processing to link with centralized databases for long-term monitoring and research. Eco Data Analyser generates ecological parameters and automates biodiversity reporting, therefore enhancing administrative efficiency and providing essential biodiversity health data for conservationists. Promoting data-driven decision-making for terrestrial ecosystem conservation and sustainability, this modular and scalable ecological data management system
Keywords: Modular Design; data analysis; data-driven decision making; long-term monitoring